Analysis of Running in Wilson's Disease - Sara Samadzadeh; Harald Hefter; Osman Tezayak; Dietmar Rosenthal (MDPI AG, 2022)
Aim of the study was to analyze the ability of long-term treated patients with Wilson's disease (WD) to run a distance of 40 m. 30 WD-patients from a single center were consecutively recruited. All patients were able to walk a distance of 40 m without walking aids. Vertical ground reaction forces (GRF-curves) were analyzed by means of an Infotronic® gait analysis system (CDG®) and correlated with clinical and laboratory findings. Results of the WD-patients were compared to those of an age-and sex-matched control group. 25 of the 30 WD-patients were able to run. Patients being unable to run had a significantly (p < 0.03) higher non-motor score. In comparison to the controls speed of running was significantly (p < 0.02) reduced in WD-patients. Their duration of foot contact on the ground lasted significantly (p < 0.05) longer. Running was more irregular in WD and the variability of times to peak of the GRF-curves was significantly (p < 0.05) increased. All running parameters extracted from the GRF-curves of the CDG® did not correlate with severity of WD. Cadence of running was significantly (p < 0.03) negatively correlated with serum liver enzyme levels. Running appears to be rather unimpaired in long-term treated WD, only 16% of the 30 WD-patients were unable to run. This knowledge is highly relevant for the patient management, but because of the missing correlation with severity of WD, analysis of running is of minor importance for monitoring WD-therapy.